Cost and sensitivity of restricted active‐space calculations of metal L‐edge X‐ray absorption spectra. Issue 5 (27th October 2015) - Pinjari, Rahul V.; Delcey, Mickaël G.; Guo, Meiyuan; Odelius, Michael; Lundberg, Marcus
Abstract : The restricted active‐space (RAS) approach can accurately simulate metal L‐edge X‐ray absorption spectra of first‐row transition metal complexes without the use of any fitting parameters. These characteristics provide a unique capability to identify unknown chemical species and to analyze their electronic structure. To find the best balance between cost and accuracy, the sensitivity of the simulated spectra with respect to the method variables has been tested for two models, [FeCl6 ] 3– and [Fe(CN)6 ] 3– . For these systems, the reference calculations give deviations, when compared with experiment, of ≤1 eV in peak positions, ≤30% for the relative intensity of major peaks, and ≤50% for minor peaks. When compared with these deviations, the simulated spectra are sensitive to the number of final states, the inclusion of dynamical correlation, and the ionization potential electron affinity shift, in addition to the selection of the active space. The spectra are less sensitive to the quality of the basis set and even a double‐ ζ basis gives reasonable results. The inclusion of dynamical correlation through second‐order perturbation theory can be done efficiently using the state‐specific formalism without correlating the core orbitals. Although these observations are not directly transferable to other systems, they can, together with a cost analysis, aid in the design of RAS models and help to extend the use of this powerful approach to a wider range of transition metal systems. © 2015 Wiley Periodicals, Inc. Abstract : With an appropriate choice of active space, basis set, and computational procedure, the restricted active space approach can be used to simulate metal L‐edge X‐ray absorption spectra with reasonable accuracy and computational cost. The sensitivity of the simulated results with respect to geometrical changes opens up for analysis of dynamical processes.